Kounis Syndrome: Dexketoprofen-Associated ST-Elevation Myocardial Infarction - Aytekin Aksakal (SMC MEDIA SRL, 2021)
Allergic angina and allergic myocardial infarction are common diseases associated with acute coronary syndromes and encompass a wide spectrum of mast cell activation disorders termed "Kounis Syndrome". We present here a patient with Kounis syndrome presenting with sudden cardiac arrest after intravenous infusion of dexketoprofen in the emergency room.